EUS-Guided Portal Pressure Gradient Measurement in Patients with Portal Hypertension: Evidence-Based Case Report - Hidayat, Putra Nur; Kurniawan, Juferdy (The Indonesian Society for Digestive Endoscopy, 2022)
Aim: This evidence-based case report aims to assess the accuracy of EUS-PPG measurement in patients with portal hypertension.Method: A literature search was performed using PubMed, Cochrane, ProQuest, and EBSCO. A total of 2 articles were selected after meeting the inclusion and exclusion criteria. Critical study assessment was conducted to assess the validity, importance, and applicability of the study.Results: As a result, the first study found higher EUS-PPG measurement values in patients with clinical parameters of portal hypertension and the second study found a good correlation between EUS-PPG measurement values with hepatic vein pressure gradient (HVPG) and transjugular intrahepatic portosystemic shunt (TIPS) portal pressure gradient (PPG).Conclusion: From these two studies, it can be concluded that EUS-PPG measurement is a safe, effective, and feasible method to be performed on patients.